Wenancjusz Fortunat, Wiersze opisowo-laudacyjne (Carmina I 19; I 20; III 12, CPL 1033) - Gacia, Tadeusz; Adamiak, Jarosław; Budzeń, Anna; Kowalczyk, Emilia; Szurgot, Dominik; Turkiewicz, Natalia (Vox Patrum, 2018)
nie dotyczy